2017
DOI: 10.4236/oalib.1103384
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Aspects of Atrial Fibrillation in a Tertiary Hospital in a Sub-Saharan Africa Setting

Abstract: Background: Atrial fibrillation (AF) is the most frequent sustained arrhythmia. The prevalence is increasing with that of other cardiovascular risk factors in our low-income setting. It is potentially serious due to the associated complications. Few data exist on the epidemiology of AF in Sub-Saharan Africa (SSA 2/8OALib Journal patients. Conclusion: Atrial fibrillation was seen in seven percent of patients in the Cardiology Unit of this low-income setting. Patients were relatively young compared with high i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
1
3
0
2
Order By: Relevance
“…It is well known that the risk of AF increases with age and is higher in patients with cardiovascular diseases and cardiovascular risk factors such as hypertension, diabetes mellitus, obesity, smoking, and alcohol abuse [24]. The majority of our AF patients had severe structural heart disease (93.1%) with hypertensive heart disease being the most prevalent and that is consistent with findings from SSA [5, 6, 22]. Hypertension was the most common risk factor of AF (59.41%) as stated by previous reports [4, 22, 2527].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…It is well known that the risk of AF increases with age and is higher in patients with cardiovascular diseases and cardiovascular risk factors such as hypertension, diabetes mellitus, obesity, smoking, and alcohol abuse [24]. The majority of our AF patients had severe structural heart disease (93.1%) with hypertensive heart disease being the most prevalent and that is consistent with findings from SSA [5, 6, 22]. Hypertension was the most common risk factor of AF (59.41%) as stated by previous reports [4, 22, 2527].…”
Section: Discussionsupporting
confidence: 89%
“…This present prospective cohort study was the first one to provide a hospital-based prevalence of AF (5.9%) in rural Burkina Faso. Previous studies in SSA have reported comparable findings however in urban populations [5, 6, 19]. In a rural Ghana, AF was reported to be scarce in a traditional African community accounting for 0.3% of 924 individuals aged of 50 years and above [20].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…8 Outros estudos em países de baixa renda mostraram também resultados similares aos nossos no que concerne a frequência e idade. [22][23][24] A ocorrência de FA necessita de melhor compreensão e esclarecimento em países de baixa e média renda. Alguns factores como o tratamento inadequado, a sub-notificação de casos e a predisposição genética poderão estar na base para a baixa prevalência e incidência relatada na região africana.…”
Section: Resultsunclassified
“…
This thromboembolic risk is assessed using the CHA 2 DS2-VASc score prior to anticoagulation [29][30][31].
…”
mentioning
confidence: 99%